Union endurance of adhesive systems in humid dentin and dry dentin: integrative review (Research, Society and Development, 2021)
Adhesion to dentin is difficult because it is a structure with high water composition, over the years the clinical protocols, as well as the adhesive systems have been changed, in order to improve the union endurance and simplify the technique. Through a integrative review, discuss the union endurance of adhesive systems in wet and dry dentin in order to improve clinical protocols. The selection of articles was carried out through the virtual health library (VHL), obtaining articles from the MEDLINE, LILACS, Biblioteca Brasileira de Odontologia (BBO) databases, in addition to searches on Google® Scholar, using the indexed terms: “Dentin”, “Dentina”, "Dentin-Bonding Agents" and “Adesivos dentinários”. Articles published between 2013 and 2020 were included. The selected studies could be clinical or laboratory, in wet and dry dentin, using tensile, microtensile or shear strength tests in the studies in vitro, with conventional, self-etching and / or universal adhesive systems, published as short articles, posters or literature reviews were excluded. 969 were found, 8 articles were selected according to the inclusion criteria, all studies addressed the degree dentin moisture content as a limiting factor in the quality of adhesion, as well as the operator's knowledge about the composition of the adhesive system used. Universal adhesive systems were effective on both wet and dry dentin, conventional adhesive systems were efficient only on wet dentin.